Mandarin language learning for education for sustainability to promote global citizenship and cultural understanding - Jafri, Nuraini; Muchen, Li (Human Resource Management Academic Research Society, 2024)
This conceptual paper examines the integration of Mandarin language learning into Education for Sustainability (EfS), proposing a framework that aligns language education with sustainability goals. As global challenges such as climate change, social equity, and economic sustainability intensify, the ability to communicate across cultures, particularly in Mandarin, is becoming increasingly crucial. The paper highlights how Mandarin can be used to foster global citizenship, enhance cultural understanding, and promote sustainable development. It proposes strategies for integrating sustainability themes into Mandarin curricula, including interdisciplinary teaching methods, project-based learning, and the use of real-world sustainability case studies. Key recommendations include the development of EfS-aligned teaching resources, the inclusion of sustainability principles in teacher education, and the creation of international collaborations with Mandarin-speaking regions. The paper also advocates for community engagement and the use of technology to enhance learning experiences. By integrating sustainability into Mandarin language education, the paper argues that students can acquire both linguistic skills and the global competencies necessary to address pressing environmental and societal challenges. It offers a transformative approach to language learning that not only enriches students' academic and cultural experiences but also prepares them to contribute meaningfully to a sustainable future.